“Why did you create this white elephant?”: Amos's Narrative Voices Cohere Under the Lens of a Metaphor-Oriented Positioning Analysis - Kupferberg, Irit (Narrative Works)

(untitled) (The University of New Brunswick, 2014)
This article focuses on Amos’s self-construction as it is identified, described, and interpreted under the lens of a metaphor-oriented positioning analysis presented here. Following a functionalist approach to discourse, discursive psychology, and a discourse-oriented approach to the study of metaphor, the study explores how Amos positions himself in his life story in the specific context of the interview. The analysis shows that the narrator produces various voices that cohere when we take into consideration his age and physical limitations as well as the contingent demands of the ongoing face-to-face interaction. In the discussion, both the findings of the present study as well as the level analysis that is proposed are interpreted and evaluated.